Enabling the Encoding of Manuscripts within the DTABf: Extension and Modularization of the Format - Susanne Haaf; Christian Thomas (Journal of the Text Encoding Initiative)
This paper presents work in progress on the DTA “Base Format” for Manuscripts (DTABf-M), an extension to the DTA “Base Format” (DTABf) for the TEI-conformant annotation of manuscripts. The DTABf is a TEI-subset for the consistent, yet unambiguous, annotation of large amounts of historical text. During our work on the DTA corpora, the DTABf has continuously been subject to further adaptations to specific annotation needs. The latest addition, the DTABf-M, contains elements, attributes, and values necessary for the annotation of (historical) handwritten documents. The goal is to provide a TEI format for diverse manuscripts in large text corpora. While the DTABf covers a wide range of phenomena found not only in printed texts but also in manuscripts, there are certain manuscript-specific features which have to be additionally represented by the DTABf-M. There are several prerequisites for DTABf-M to be suitable for the DTA and its workflows and processes: First, it should be based on the original DTABf tagset, and only extend it if unavoidable. Second, like the DTABf, the DTABf-M should be created in a bottom-up approach, that is, based on actual phenomena found in handwritten texts which are transcribed and encoded using the DTABf. Third, the format should complement the DTABf, not replace it. Hence, it is necessary to find a modular way of integrating the DTABf-M into the DTABf. This paper describes how we deal with these issues in the process of developing the DTABf-M.